Plant species visited by honey bee foragers during induced cantaloupe pollination - Reyes-Carrillo, José Luis; Eischen, Frank A.; Cano-Rios, Pedro; Rodríguez-Martínez, Rafael; Nava-Camberos, Urbano (Instituto de Ecología, A.C., 2009)
The purpose of the research was to determine, by identifying pollen in corbicular pellets, the different plant species visited by honeybees (Apis mellifera L.) during cantaloupe (Cucumis melo L.) induced pollination. This work was carried out in La Laguna region, located in the states of Coahuila and Durango, Mexico in the spring of 2003. During the first 31 days of cantaloupe bloom, 18 honey bee colonies were placed in a six ha field, nine of which had a bottom pollen trap. Trapped pollen was collected twice per a week weighed and frozen. Through the year, anthers of wild and cultivated flowering plant species around the cantaloupe field and in La Laguna were collected, acetolyzed and preserved for pollen identified. Corbicular pollen from the 5th, 9th, 12th, 20th, 24th and 31st sample dates after start of staminate bloom was processed, identified and counted by microscopy. Pollen size was calculated with the formula: volume V=?a2b where a is the major axe and b the minor axis and multiplied by the number of pollen grains to get the total volume. Cantaloupe pollen made up 8.7 %, 9.8%, 17.6 %, 9.3 %, 28.1% and 83.5% of that collected (number of pollen grains) on respectively for the sample dates. The percentage of volume basis pollen for cantaloupe was: 51.6%, 85.0%, 66.6 %, 84.4 %, 68.9% and 95.0% respectively. It is concluded that the cantaloupe was the main species visited as a plant pollen source for pollinating honeybees and that the plants present in the sample like mesquite (Prosopis juliflora (Swartz) DC.), alfalfa (Medicago sativa L.), creosote bush (Larrea tridentata (DC) Cov.), cucumber (Cucumis sativus L.), London rocket (Sysimbrium irio L.) and sorghum (Sorghum vulgare L.) were species visited as supplementary pollen sources.